2016
DOI: 10.1097/pas.0000000000000714
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reproducibility of Percent Gleason Pattern 4 in Prostatic Adenocarcinoma on Prostate Biopsies

Abstract: In the WHO Classification of Tumours of the Urinary System and Male Genital Organs published in 2016, it was officially recommended that the percent of Gleason pattern 4 (GP4) be reported on pathology reports to better reflect the extent in Gleason score 7 tumors. In this study we assessed the reproducibility of reporting GP4 on prostate biopsies. We analyzed prospectively 422 cores containing GP4 from our consult cases over a period of 2.5 months. The percent pattern 4 was assigned to all the cases in 10% inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
0
35
2
Order By: Relevance
“…Nonetheless, MAI did not significantly correlate with the pathological outcome, which is the Gleason score in our database. Inter-observer differences in Gleason grading between the training and the testing database could already contribute to this discrepancy, albeit minimally, as previous studies have shown negligible inter-observer variation mostly at the upper and lower limit, namely 4 and 8–10 of the Gleason scale [43,44]. Another possible variability factor may rely on the classifier´s training on whole slide pathology specimens, whereas the grading process in the current study was based on needle biopsies [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, MAI did not significantly correlate with the pathological outcome, which is the Gleason score in our database. Inter-observer differences in Gleason grading between the training and the testing database could already contribute to this discrepancy, albeit minimally, as previous studies have shown negligible inter-observer variation mostly at the upper and lower limit, namely 4 and 8–10 of the Gleason scale [43,44]. Another possible variability factor may rely on the classifier´s training on whole slide pathology specimens, whereas the grading process in the current study was based on needle biopsies [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the percent Gleason pattern 4 is relatively reproducible, with substantial agreement within ± 10% in cases. 48 Cases where patterns 3 and 4 are intermingled are more difficult to assess for percent pattern 4. 49 We have shown that there is only moderate interobserver agreement for assessing the percent pattern 4 with o 10% involvement of the core by cancer, as a few glands of a given pattern can markedly affect the percent of Gleason pattern 4.…”
Section: Reporting Percentage Patternmentioning
confidence: 99%
“…49 We have shown that there is only moderate interobserver agreement for assessing the percent pattern 4 with o 10% involvement of the core by cancer, as a few glands of a given pattern can markedly affect the percent of Gleason pattern 4. 48 As a result, some experts do not record percent pattern 4 in small foci of Gleason score 7 tumors on needle biopsy, although other experts routinely reports percent pattern 4 for call cases of Gleason score regardless of tumor extent.…”
Section: Reporting Percentage Patternmentioning
confidence: 99%
“…One study reported that interobserver reproducibility of percent Gleason grades 4 or 5 on prostate biopsies is at least as good as that of Gleason score . A subsequent reproducibility study on percentage Gleason grade 4 in prostate biopsies revealed that when reported in 10% increments, 32% had an exact match between fellow and expert urological pathologist and 75% were within a 10% range with a good (weighted kappa of 0.67) agreement . The agreement for percentage Gleason pattern 4 decreased significantly only when carcinoma comprised 10% or less of the core.…”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%